Research on household emergency supplies storage from the theory of planned behavior and intention-behavior gap in the context of COVID-19 - Wang, Luyan; Jiang, Yuan; Pan, Liujun; Ji, Jiangyuan; Xu, Aoao (Frontiers in Psychology, 2023)
Abstract: In the context of COVID-19 epidemic, household-level emergency supplies are becoming a critical link in the national emergency response mechanism for public health emergencies. Based on the theory of planned behavior, this study explored the influencing factors of residents' household emergency supplies storage, and introduced community institutional trust and community network as moderating variables to analyze the process of transformation of residents' household emergency supplies storage intentions to behaviors from the perspective of community situation, and initially constructed a two-stage integration model including intention formation and behavior transformation. The study found that subjective norms and perceived behavioral control had a positive impact on residents' intention to store emergency supplies, while attitudes did not play a significant role. Community institutional trust and community network play significant moderating roles in the transformation from intentions to behaviors. By analyzing the forming process of household emergency supplies behavior, this paper revealed the effective paths for the formation of household emergency supplies storage intention, and put forward policy suggestions from the government and community levels.